DIMENSIONS OF MIDWIVES’ SATISFACTION WITH THE MANUAL BOOK OF THE MATERNAL EMERGENCY REFERRAL SYSTEM IN THE ISLANDS (SIRUTAN) - Darwitri, Darwitri; Melly Damayanti; Ristina Rosauli Harianja; Metasari Sihaloho; Nurul Aini Suria Saputri; Tiyara Safitri (International Journal of Social Science, 2025)
This study aims to evaluate the satisfaction of midwives with the manual book of the Maternal Emergency Referral System in the Islands (Si-RUTAN) in supporting effective maternal emergency care in remote island regions. A cross-sectional descriptive study was conducted involving 30 midwives from public health centers across the Riau Islands Province in 2024. In addition, the manual was evaluated by an obstetrics and gynecology expert (SpOG) using Nielsen's heuristic usability principles. The data were analyzed using univariate descriptive statistics. Most midwives reported high satisfaction with the manual: 83.3% were "very satisfied" and 16.7% "satisfied". Across all SERVQUAL dimensions, the majority rated their satisfaction as "very satisfied", particularly in Responsiveness (80%) and Assurance (80%). No respondents reported dissatisfaction. Heuristic evaluation by the expert yielded consistently high scores, especially in "Match with real-world scenarios" and "Help and documentation" (mean score = 4.8). The expert confirmed the manual's clarity, relevance, and usability in maternal emergency situations.Conclusion:The Si-RUTAN manual book is a well-received, context-appropriate resource for midwives working in island regions. Its effectiveness in facilitating maternal emergency referrals and high usability rating suggest it should be promoted and continuously refined through user and expert input.